The Effect of Online Reviews and Location on Purchase Decisions with Purchase Intention as a Mediating Variable in Seafood MSMEs at Nyoman Café Jimbaran (Pusat Riset dan Inovasi Nasional, 2026)
The rapid advancement of digital technology has transformed consumer behavior in information searching and purchasing decisions, particularly within the tourism-based culinary sector. In highly competitive markets with relatively homogeneous products, non-product factors such as online reviews and business location play an increasingly important role in shaping consumer choices. This study aims to analyze the influence of online reviews and location on purchase decisions, with purchase intention as a mediating variable, focusing on the seafood MSME Nyoman Cafe Jimbaran. The research adopts a quantitative approach using a survey method. Data were collected through online and offline questionnaires from 200 respondents who had accessed online reviews of Nyoman Cafe Jimbaran. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS, including evaluation of the measurement model, structural model analysis, and testing of direct and indirect effects. The results indicate that online reviews and location have a positive and significant impact on purchase decisions, while location also significantly influences purchase intention. However, online reviews do not significantly affect purchase intention, and purchase intention does not significantly influence purchase decisions. Furthermore, purchase intention does not mediate the relationship between online reviews or location and purchase decisions. These findings suggest that in culinary tourism contexts, purchasing decisions tend to be spontaneous and are more directly driven by digital reputation and strategic location. This study contributes to digital consumer behavior literature and provides practical insights for culinary MSMEs.